The Total Phenolic, Total Flavonoid, and Brown Pigment in Honey Before and After Heating - Achmad Tjachja Nugraha; La Ode Sumarlin; Anna Muawanah; Nurul Amilia; Meyliana Wulandari (Elkawnie, 2022)
Abstract: Honey has unique components, a characteristic that makes it a valuable food for consumers. It is known that UV radiation and heating impact the quality of honey's bioactive compounds, including total phenolic, total flavonoid, and brown pigment contents. The absorbance of brown pigment at a wavelength of 420 nm, total phenolic at a wavelength of 733 nm, and total flavonoid at a wavelength of 430 nm was measured using a UV-Vis spectrophotometer. The method used in the total phenolic test was the Folin-Ciocalteu method with gallic acid standard (mgGAE/g sample). In contrast, for flavonoids, the method used was the colorimetric method with quercetin standard (mg QE/g sample). The qualitative test results showed that all honey samples contained phenolic and flavonoid compounds. Total phenolic and flavonoid levels showed a decrease in several samples, including TR SLT (Trigona Southeast Sulawesi), TRG BGR (Trigona Bogor), and TR SLS (Trigona Genotrigona Indica South Sulawesi) in the range of 11.8–57.6%. However, most of the total phenolic and flavonoid levels increased after the heating process, i.e., in the samples of AP LMB (apis North Lombok) (25.3% and 88.8%), AP MG (apis mango) (73.1% and 114%), AP MAC (Aceh honey, Buloh Seuma) (8.8% and 199%), TR BIR (Trigona tetroginola biroi South Sulawesi) (58.8% and 146%), and TR LMB (Trigona North Lombok) (44.3% and 84.9%). In contrast, for the formation of brown pigment, there was an increase in all honey samples between 32 and 1.428%. The presence of brown pigment at the end of the heating process of honey samples is thought to have the same role as phenolic compounds and flavonoids, which change the heating process, especially in antioxidant activities and other bioactivities. However, further analysis is needed to prove the conjecture.Abstrak: Madu memiliki komponen yang unik, yang membuatnya menjadi makanan yang berharga bagi konsumen.  Telah diketahui bahwa radiasi UV dan pemanasan berdampak pada kualitas senyawa bioaktif madu, di antaranya kandungan total fenolik, total flavonoid, dan pigmen coklat. Pengukuran absorbansi pigmen coklat pada panjang gelombang 420 nm, pengukuran total fenolik pada panjang gelombang 733 nm dan total flavonoid pada panjang gelombang 430 nm dilakukan menggunakan spektrofotometer UV-Vis. Metode yang digunakan untuk uji total fenolik adalah metode Folin-Ciocalteu dengan standar asam Galat (mgGAE/g sampel), uji flavonoid menggunakan metode Kolorimetri dengan standar kuersetin (mg QE/g sampel).  Hasil uji kualitatif menunjukan bahwa semua sampel madu terdapat senyawa fenolik dan flavonoid. Kadar total fenolik dan flavonoid menunjukkan penurunan pada beberapa sampel, di antaranya TR SLT (Trigona Sulawesi Tenggara, TRG BGR (Trigona Bogor), TR SLS (Trigona Genotrigona Insica Sulawesi Selatan) pada kisaran 11,8 – 57,6%.  Namun, sebagian besar kadar total fenolik dan kadar flavonoid mengalami kenaikan setelah proses pemanasan, yaitu pada sampel AP LMB (apis Lombok Utara) (25,3% dan 88,8%), AP MG (apis mangga) (73,1% dan 114%), AP MAC (madu Aceh, Buloh Seuma) (8,8% dan 199%), TR BIR (Trigona Tetroginola biroi sulawesi selatan) (58,8% dan 146%), TR LMB (Trigona North Lombok) (44,3% dan 84,9), sedangkan untuk pembentukan pigmen coklat, terjadi peningkatan pada semua sampel madu di antara 32 – 1.428%. Keberadaan pigmen coklat pada akhir proses pemanasan, diduga memiliki peran yang sama dengan senyawa fenolik dan flavonoid yang mengalami perubahan selama proses pemanasan, terutama pada aktivitas antioksidan dan bioaktivitas lainnya.  Namun diperlukan analisis lebih lanjut untuk membuktikan dugaan tersebut.